Growth retardation in glioma cells cocultured with cells overexpressing a gap junction protein. - Zhu, D (1992)
To examine the role of gap-junctional intercellular communication in controlling cell proliferation, we have transfected C6 glioma cells with connexin 43 cDNA. The growth of transfected clones was dramatically reduced compared with nontransfected glioma cells. To further characterize the role of gap junctions in controlling proliferation, we have examined the growth of C6 cells cocultured with transfected cells overexpressing connexin 43. Although C6 cells grew at their normal rate when cocultured with nontransfected C6 cells, when cocultured with connexin 43-overexpressing cells they displayed a dramatic reduction in growth rate. Furthermore, a significant, dose-dependent reduction in cell proliferation was noted when C6 cells were cultured in medium conditioned by transfected cells. This effect correlated with the level of connexin 43 expression. These results suggest that the decreased cell proliferation rate of transfected cells and C6 cells cultured with them is due to the secretion of a growth inhibitory factor(s) and that the secretion of this factor may be linked to the level of gap junctional intercellular communication.